How far does school effectiveness come from? - J. Bonifacio Barba Casillas (Universidad Autónoma de Madrid, 2018)
Research on school effectiveness (IEE) has been a fruitful field of work, but in the field of values training and moral development has one of its most important challenges. Due to the fact that the IEE has shown that the school does matter and that the work of the teachers is very relevant (Cf. Murillo, 2008), the expectation of improving the school has increased, both because of what she can do with the whole of its institutional resources, as well as the responsibility of societies and governments to give it the maximum support to meet its mission, as indicated in the Constitutions of the countries and various diagnostic and educational policy documents prepared by agencies multilateral.